Intimate partner violence during pregnancy and perinatal mental disorders in low and lower middle income countries: A systematic review of literature, 1990–2017 - Halim, Nafisa; Beard, Jennifer; Mesic, Aldina; Patel, Archana; Henderson, David; Hibberd, Patricia (Clinical psychology review, 2018)
Mental health consequences of intimate partner violence (IPV) against pregnant and postpartum women are poorly understood in low and lower-middle-income countries (LLMIC). We systematically reviewed the evidence from 24 studies (1990—2017) selected via a comprehensive search strategy with 14 inclusion, exclusion, and quality-control criteria to assess the extent to which intimate partner violence during pregnancy adversely affects perinatal mental disorders among participants in 10 LLMIC across 4 economic regions. Mostly cross-sectional, studies included 61—1369 participants selected randomly (88%) or non-randomly (12%) from purposively selected 1—6 clinics or 1—50 communities. Multivariate logistic regression was most frequently used (68%) for association estimates, adjusting for 3—16 socio-demographic variables pertinent to: women; husbands; and/or households. The prevalence of physical IPV ranged 2—35% among participants; sexual IPV ranged 9—40%; and psychological IPV ranged 22—65%. The prevalence of antenatal and postnatal depression ranged 15—65% and 5—35% among participants, respectively. Suicidal ideation ranged 5—11% during pregnancy and 2—22% during the postpartum period. Study participants who had experienced IPV had 1.69—3.76 and 1.46—7.04 higher odds of antenatal and postnatal depression compared to those who had not, depending on country, and IPV type and severity. Considering the strong association between IPV and mental disorders, efforts should focus on developing IPV interventions aimed at preventing pregnancy during IPV and promoting mental health resilience among pregnancy and postpartum women in low and lower-middle-income countries. •We reviewed 24 studies (1990–2017) selected via 14 criteria to assess effects of IPV during pregnancy on perinatal mental disorders in 10 LLMIC.•The prevalence of physical IPV ranged 2–35% in participants across LLMIC; sexual IPV ranged 9–40%; and psychological IPV ranged 22–65%.•Depression ranged 15–65% during pregnancy and 5–35% during the postpartum period.•Suicidal ideation ranged 5–11% during pregnancy and 2–22% during the postpartum period.•Pregnancy IPV increases odds of ante- and postnatal depression by 1.69–3.76 and 1.46–7.04, respectively, depending on IPV type and severity.